Uji Aktivitas Penangkapan Radikal Bebas Ekstrak Etanol Daun Mangkokan (Nothopanax scutellarium (Burm.f) Merr.) Menggunakan Metode DPPH (1,1-Difenil-2-Pikrilhidrazil) dengan Variasi Suhu Pengeringan - farida, fitri; guntarti, any (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2017)
Mangkokan leaves contains flavonoids that are known as natural antioxidant source. The aim of this study is to find the effect of drying temperature variations towards free radical scavenging activity of mangkokan leaves. Mangkokan leaves macerated with 96% ethanol and dried at 40oC, 50oC, and 60oC. Then were macerated with ethanol 96%. Antioxidant activity tested by DPPH method and quercetin was used as positive control. Dry shrinkage with temperatures at 40oC, 50oC, and 60oC were: (9.25 ± 0.276)%; (8.76 ± 0.348)% and (7.97 ± 0.372)%, respectively. Water content at 40oC, 50oC and 60oC were: (5.13 ± 0.575)%; (4.53 ± 0.512)% and (4.04 ± 0.575)%, respectively. The antioxidant potency of 96% ethanolic mangkokan leaves by ES50 value at drying temperatures 40oC, 50oC, 60oC and quercetin were (1.75 ± 0.058); (2.39 ± 0,089); (5.38 ± 0,078) mg/ml and (9.16x10-4 ± 4.36x10-5) mg/ml. Ethanolic extract of mangkokan leaves which dried at 40oC has biggest radical DPPH scavenging activity but much weaker than quercetin.